Coeliac disease and risk of tuberculosis: a population based cohort study. Issue 1 (17th October 2006) - Ludvigsson, J F; Wahlstrom, J; Grunewald, J; Ekbom, A; Montgomery, S M
Abstract : Background: Coeliac disease (CD) is an autoimmune disease often characterised by malnutrition and linked to a number of complications such as an increased risk of lymphoma, adverse pregnancy outcome, and other autoimmune diseases. Tuberculosis (TB) affects a large proportion of the world population and is more common in individuals with malnutrition. We investigated the risk of TB in 14 335 individuals with CD and 69 888 matched reference individuals in a general population based cohort study. Methods: Cox proportional hazards method was used to calculate the risk of subsequent TB in individuals with CD. In a separate analysis, the risk of CD in individuals with prior TB was calculated using conditional logistic regression. Results: CD was associated with an increased risk of subsequent TB (hazard ratio (HR) 3.74, 95% CI 2.14 to 6.53; p<0.001). Similar risk estimates were seen when the population was stratified for sex and age at CD diagnosis. Individuals with CD were also at increased risk of TB diagnosed in departments of pulmonary medicine, infectious diseases, paediatrics, or thoracic medicine (HR 4.76, 95% CI 2.23 to 10.16; p<0.001). The odds ratio for CD in individuals with prior TB was 2.50 (95% CI 1.75 to 3.55; p<0.001). Conclusions: CD is associated with TB. This may be due to malabsorption and lack of vitamin D in persons with CD. Individuals with TB and gastrointestinal symptoms should be investigated for CD.